The influence of consumer pressure & employee pressure on the quality of sustainability report disclosure - Safitri, Elvira Dewi; Alvia, Liza (Asian Journal of Applied Business and Management, 2024)
The main goal of a sustainability report is to promote transparency among stakeholders like consumers and investors, allowing companies to assess their performance and identify areas for improvement. However, many companies overlook environmental impact, leading to practices that harm the environment. This study uses hypothesis testing to explore the connection between different variables. Data was gathered from all ASSRAT 2020-2022 companies using purposive sampling criteria. The findings reveal that consumer behavior significantly impacts sustainability report quality, as does stakeholder behavior. Understanding these relationships provides valuable insights for companies to enhance their sustainability reporting by incorporating feedback from various stakeholders.